Self-Control as an Intervening in The Determinants of Consumptive Behavior of Paylater Use - Nur Lailiyatul Inayah; Ali Muhdor; Ruci Arizanda Rahayu (Research Parks Publishing LLC, 2026)
The development of digital technology has influenced consumer behavior, especially among Millennials and Generation Z, through the convenience of payment services such as PayLater. This study aims to analyze the influence of financial literacy, lifestyle, and risk on the consumptive behavior of PayLater users, with self-control as a mediating variable. A quantitative approach was employed with a sample of 96 respondents from Sidoarjo District, selected using the Lemeshow formula. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results show that financial literacy, lifestyle, and risk significantly influence both consumptive behavior and self-control. Furthermore, self-control has a significant impact on consumptive behavior and successfully mediates the relationship between the three independent variables and consumptive behavior. These findings highlight the importance of self-control in mitigating the negative effects of PayLater usage and the need to enhance financial literacy and promote a financially responsible lifestyle.